FOLFOX plus anti-epidermal growth factor receptor (EGFR) monoclonal antibody (mAb) is an effective first-line treatment for patients with RAS-wild left-sided metastatic colorectal cancer: A meta-analysis. Issue 10 (March 2018) - Chen, Datian; Li, Li; Zhang, Xiang; Gao, Guangyi; Shen, Lili; Hu, Jing; Yang, Mi; Liu, Baorui; Qian, Xiaoping
Abstract: Background: The efficacy of oxaliplatin-based chemotherapy combined with anti-epidermal growth factor receptor (EGFR) monoclonal antibody (mAb) remains controversial in metastatic colorectal cancer (mCRC). This meta-analysis aims to estimate the effect of adding panitumumab or cetuximab to oxaliplatin-based chemotherapy in RAS wild type mCRC patients for the first-line treatment. The primary tumor location is also considered into this meta-analysis. Methods: RCT studies were identified by a search of MEDLINE, EMBASE, Cochrane library to October 2017, supplemented by manually retrieving ASCO, ESMO conference abstracts. The pooled hazard ratio (HR) for progression-free survival (PFS) and overall survival (OS), and pooled odds ratios (OR) for the overall response rate (ORR) were calculated by Review Manager 5.3. Results: The results indicated that the addition of anti-EGFR mAbs to FOLFOX regimen in RAS wild-type mCRC patients for the first-line treatment resulted in considerable improvements in PFS (HR = 0.70; 95% confidence interval [CI]: 0.59–0.82; P < .0001), OS (HR = 0.79; 95%CI: 0.67–0.92; P = .003), and ORR (OR = 2.56; 95% CI: 1.77–3.70; P < .00001) compared with chemotherapy alone. However, in RAS/BRAF wild patients, no significant differences were observed when anti-EGFR mAb was added to FLOX or XELOX regimen compared with chemotherapy alone with regard to OS and PFS, whereas FOLFOX+anti-EGFR mAb showed a marked superior OS and PFS (OS, HR = 0.77; 95% CI: 0.61–0.98; P = .03; PFS, HR = 0.68; 95% CI: 0.57–0.82; P < .00001). A meta-analysis including TAILOR and PRIME study suggests that primary tumor location (PTL) predicted a survival benefit when adding the EGFR antibody to FOLFOX regimen in RAS-wild mCRC patients (OS, HR for left-sided: 0.71; 95% CI: 0.59–0.85; P = .0002 and HR for right-sided: 0.90; 95% CI: 0.65–1.25; P = .53). However, the HR for PFS and ORR still suggests a benefit from the addition of anti-EGFR mAb in right-sided mCRC patients. Conclusion: So these results suggest anti-EGFR mAb and oxaliplatin are good partners in the FOLFOX regimen. The addition of EGFR antibody to FOLFOX markedly improved efficacy in RAS-wild patients with left-sided mCRC. In RAS/BRAF-wild patients, the efficacy is similar. For patients with right-sided tumor, a benefit showing a trendency in favor of anti-EGFR mAb can still seen. The molecular characteristics behind the tumor location need to be more explored urgently.